The Ethnic Division of Labour in Montreal from 1931-1951 - Rennie, D. L. C. (Douglas Lloyd Claver) (McGill University, 1953)
The people who live in the City of Montreal are exceedingly various. There are officially two languages and unofficially dozens. Many areas of the city provide examples of "culture islands"–Those fast-disappearing settlements of "alien" peoples who preserve their alien ways of life in a new country, and so impart to the latter "atmosphere" and "flavour". To serve and satisfy the various demands of these people there are many and different institutions making it possible for individuals, if they wish, to live their entire lives in their native atmospheres.